Kolaborasi Lintas Sektor Dalam Pelatihan Teknik Pemasaran dan Pemanfaatan Teknologi Digital Bagi UMKM di Kota Lhokseumawe - Maryam; Aiyub; Muryali; Saharuddin; Ade Muana Husniati; Maisyura (Universitas Malikussaleh, 2026)
Digital marketing training and the use of digital technologies have become essential in today’s business environment. Increasing competition requires MSMEs to adapt by improving digital literacy and skills, particularly among groups with limited prior knowledge. In this context, stakeholders play a strategic role in providing knowledge, facilities, and sustained support to enable MSMEs to leverage digital channels and expand market access. This article examines a digital marketing and digital technology utilization training program for MSME practitioners in Lhokseumawe City, covering training materials, implementation methods, benefits, impacts, participant feedback, and follow-up recommendations. The program aimed to strengthen basic digital competencies, especially digital marketing strategies and the use of digital media to promote processed food products, which are predominantly produced by women-led MSMEs. The training was implemented through cross-sector collaboration involving government, academia, and MSME communities. The results indicate a meaningful impact, reflected in increased participants’ understanding of digital marketing, stronger motivation to promote their businesses through digital media, and initial actions such as creating accounts on online platforms. These findings suggest that digital marketing and digital media training can serve as a driving force for strengthening MSME capacity. Therefore, similar programs should be continuously promoted to generate long-term benefits for the economic sustainability of MSMEs in Lhokseumawe City.